Strategic leadership and technological innovation: A comprehensive review and research agenda - Christopher Kurzhals; Lorenz Graf-Vlachy; Andreas König (Corporate Governance: An International Review, 2020)
Research Question/Issue We review the literature on the relationship between strategic leadership and technological innovation. Research Findings/Insights We identify the theoretical lenses that researchers apply when studying strategic leadership and innovation, most notably agency theory and upper echelons theory. We review the innovation constructs and measures that scholars employ, and we survey the links among strategic leaders' characteristics and technological innovation. Ultimately, we organize the literature into an integrative framework that provides a concise overview of the extant knowledge, and we outline an agenda for future research. Theoretical/Academic Implications First, we offer scholars a discipline-spanning overview of the extant knowledge on the topic. Second, by integrating important aspects of corporate governance, such as the role of the board of directors, incentives for the chief executive officer or the top management team, and firm ownership, into the context of technological innovation, we highlight the vital role it plays in the realm of technological innovation. Third, we provide a useful guide for scholars and direct their work towards fruitful avenues for future research. Practitioner/Policy Implications We offer insights for practitioners interested in better understanding the bidirectional relationship between strategic leadership and technological innovation. In particular, our framework and our detailed analysis of the impact of strategic leaders on technological innovation can guide shareholders and board members in matters related to board composition as well as top executive selection and compensation.
Keywords: 320; Corporate governance; innovation; strategic leadership; technology